2000
DOI: 10.1001/archopht.118.5.666
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases and Tumor Necrosis Factor α in Glaucomatous Optic Nerve Head

Abstract: To study expression and location of matrix metalloproteinases (MMPs) and tumor necrosis factor ␣ (TNF-␣) in glaucomatous optic nerve heads, which are known to be secreted in response to a variety of neuronal injury.Methods: Four postmortem eyes from patients with primary open-angle glaucoma, 7 eyes from patients with normal-pressure glaucoma, and 4 eyes from age-matched normal donors were studied by immunohistochemistry. The sections of the optic nerve heads were examined after immunostaining with antibodies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
175
0
9

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(193 citation statements)
references
References 41 publications
9
175
0
9
Order By: Relevance
“…This up-regulation exhibited a close association with the cumulative IOP exposure and neuronal damage (available at www.iovs.org, 2005; 46:EAbstract 3772). Similar to glaucomatous human eyes Yan et al, 2000), increased TNF-α immunolabeling in ocular hypertensive rat eyes compared with the controls was mainly localized to glial cells. However, retinal TNF-R1 immunolabeling in the ocular hypertensive eyes was most prominent on RGCs and their axons.…”
Section: Evidence Supporting the Role Of Tnf-α As A Mediator Of Retinmentioning
confidence: 67%
See 4 more Smart Citations
“…This up-regulation exhibited a close association with the cumulative IOP exposure and neuronal damage (available at www.iovs.org, 2005; 46:EAbstract 3772). Similar to glaucomatous human eyes Yan et al, 2000), increased TNF-α immunolabeling in ocular hypertensive rat eyes compared with the controls was mainly localized to glial cells. However, retinal TNF-R1 immunolabeling in the ocular hypertensive eyes was most prominent on RGCs and their axons.…”
Section: Evidence Supporting the Role Of Tnf-α As A Mediator Of Retinmentioning
confidence: 67%
“…Parallel studies through immunohistochemical analysis of human donor eyes revealed an increased immunolabeling for TNF-α and TNF-R1 in the optic nerve head (Yan et al, 2000) and retina ) of glaucomatous eyes compared to age-matched controls. Using in situ hybridization, mRNA signals for TNF-α or TNF-R1 were also found to be similarly more intense in glaucomatous eyes relative to controls .…”
Section: Evidence Supporting the Role Of Tnf-α As A Mediator Of Retinmentioning
confidence: 91%
See 3 more Smart Citations